Linking a cell-division gene and a suicide gene to define and improve cell therapy safety. (29th November 2018) - Liang, Qin; Monetti, Claudio; Shutova, Maria; Neely, Eric; Hacibekiroglu, Sabiha; Yang, Huijuan; Kim, Christopher; Zhang, Puzheng; Li, Chengjin; Nagy, Kristina; Mileikovsky, Maria; Gyongy, Istvan; et al.
Abstract Human pluripotent cell lines hold enormous promise for the development of cell-based therapies. Safety, however, is a crucial prerequisite condition for clinical applications. Numerous groups have attempted to eliminate potentially harmful cells through the use of suicide genes1, but none has quantitatively defined the safety level of transplant therapies. Here, using genome-engineering strategies, we demonstrate the protection of a suicide system from inactivation in dividing cells. We created a transcriptional link between the suicide gene herpes simplex virus thymidine kinase (HSV-TK ) and a cell-division gene (CDK1 ); this combination is designated the safe-cell system. Furthermore, we used a mathematical model to quantify the safety level of the cell therapy as a function of the number of cells that is needed for the therapy and the type of genome editing that is performed. Even with the highly conservative estimates described here, we anticipate that our solution will rapidly accelerate the entry of cell-based medicine into the clinic. Introduction of a suicide gene together with a linked cell-division gene to generate a safe-cell system enables the selective elimination of proliferating cells after cell transplantation in mouse models of cell therapy.